Effectiveness of Cinnamon (Cinnamomum burmannii) Leaf Extract on Growth and Meat Quality of Farmed Fish: A Review - Rahmadani, Thoy Batun Citra; Mulyani, Laily Fitriani; Sumiana, I Kadek (Aquaculture Department, University of Mataram, 2025)
Aquaculture continues to expand globally, requiring natural and sustainable feed additives to enhance fish growth and meat quality. Cinnamon (Cinnamomum burmannii) leaf extract contains diverse bioactive compounds, including cinnamaldehyde, flavonoids, polyphenols, and terpenoids, which possess antioxidant, antimicrobial, and growth-promoting properties. This review aims to summarize scientific evidence on the effectiveness of cinnamon leaf extract in improving growth performance and meat quality of farmed fish. A systematic literature review was conducted by analyzing 41 scientific publications obtained from Google Scholar, ProQuest, and Elsevier. The reviewed studies consistently showed that supplementation of cinnamon leaf extract or powder at doses ranging from 0.25–1% in fish feed enhances growth parameters such as Specific Growth Rate, feed efficiency, protein retention, and biomass in species including barramundi, Nile tilapia, common carp, and striped catfish. In addition, the extract significantly improves meat quality by reducing body and meat fat content, enhancing texture, increasing protein levels, and improving sensory attributes such as taste and fillet color. These improvements are attributed to the metabolic, antioxidant, and lipid-modulating mechanisms of the phytochemicals present in cinnamon leaves. Overall, cinnamon leaf extract demonstrates strong potential as a natural, environmentally friendly feed additive that supports both productivity and product quality in modern aquaculture systems.